Tanggung Jawab Marketplace Terhadap Penjualan Barang Secara Online - Pattipeilohy, Quentyn Priscilla; Akyuwen, Rory Jeff (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2025)
Currently, there is a lot of use of the internet for commerce among the public which is a means of online buying and selling. It is regulated in the Civil Code, Law Number 8 of 1999 concerning Consumer Protection, Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, Government Regulation Number 8 of 2019 concerning Trading Through Electronic Systems. However, there are still many violations that are committed to the detriment of buyers and sellers. Based on this research, online marketplaces allow sellers and buyers to interact and carry out transactions online, facilitating the buying and selling process and increasing sales capabilities, but the parties involved in buying and selling on the marketplace do not comply with statutory regulations so it can be concluded that the actions that have been taken carried out by each party can cause losses to each party intentionally or unintentionally. The responsibility of the marketplace is to provide compensation and compensation for goods received that do not comply with the agreement.